ANALISIS SWOT PENENTUAN STRATEGI PEMASARAN LAYANAN INDOSAT LEASED LINE DI SURABAYA - Justinus H Kaseger; Pompong B Setiadi; Sri Rahayu (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Telecommunications has become one of the basic needs for humans, especially the people of Indonesia. The purpose of this research is to find the SWOT factors in the company and find the right marketing strategy for the company. The analytical technique used is a descriptive analysis technique, which is a data processing analysis technique by describing a situation in depth so that an overview or conclusion is obtained about the situation in question. From the research results, the following conclusions can be drawn: 1. Strengths: The quality of Leased Line products is still considered good. 2. Weaknesses: Production costs incurred by PT. Indosat to launch Leased Line Products is very big. 3. Opportunities: continue to study Leased Line competitors by exploiting competitors' weaknesses and 4. Threats:The economic crisis resulted in increased production costs